2017
DOI: 10.1103/physrevb.96.235406
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of two-dimensional epitaxial clusters on metal (100) surfaces: Facile versus nucleation-mediated behavior and their merging for larger sizes

Abstract: For diffusion of two-dimensional homoepitaxial clusters of N atoms on metal(100) surfaces mediated by edge atom hopping, macroscale continuum theory suggests that the diffusion coefficient scales like D N ~ Nβ with β = 3/2. However, we find quite different and diverse behavior in multiple size regimes. These include: (i) facile diffusion for small sizes N < 9; (ii) slow nucleation-mediated diffusion with small β < 1 for "perfect" sizes N = N p = L 2 or L(L+1), for L = 3, 4,… having unique ground state shapes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…Previous analysis of data for adatom islands for φ = 0.20 eV and δ = 0 at 300 K (using the data shown in Figure 4) revealed that the effective scaling exponent, βeff, did achieve this asymptotic value of βmacro = 1.5 for N ≥ 2300. This is consistent with the expectation that such asymptotic behavior should be achieved for linear island sizes well above the characteristic separation of kinks on close packed step edges, 24 Lk = ½ exp[½φ/(kBT)] ≈ 24 in units of 'a', i.e., for N well above (Lk) 2 ≈ 580. From Figure 4, convergence of the effective size scaling exponent to this asymptotic value for vacancy pits is somewhat slower with βeff ≈ 1.32 for 2025 ≤ N ≤ 3250.…”
Section: B Further Analysis Of Results For Dn Versus Nsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous analysis of data for adatom islands for φ = 0.20 eV and δ = 0 at 300 K (using the data shown in Figure 4) revealed that the effective scaling exponent, βeff, did achieve this asymptotic value of βmacro = 1.5 for N ≥ 2300. This is consistent with the expectation that such asymptotic behavior should be achieved for linear island sizes well above the characteristic separation of kinks on close packed step edges, 24 Lk = ½ exp[½φ/(kBT)] ≈ 24 in units of 'a', i.e., for N well above (Lk) 2 ≈ 580. From Figure 4, convergence of the effective size scaling exponent to this asymptotic value for vacancy pits is somewhat slower with βeff ≈ 1.32 for 2025 ≤ N ≤ 3250.…”
Section: B Further Analysis Of Results For Dn Versus Nsupporting
confidence: 90%
“…An assessment of the merging point is based on an assessment of when the distinct identity of different branches is lost, which in turn relies on determination of when clusters have a significant probability of being in an excited state configuration (above the T = 0 K ground state). 23,24 An appropriate combinatorial analysis in Appendix C gives results consistent with the above observations of disrupted behavior occurring earlier for smaller φ.…”
Section: B Further Analysis Of Results For Dn Versus Nsupporting
confidence: 76%
See 3 more Smart Citations